Penggunaan Design Thinking pada perusahaan Sampul Kreatif Teknologi: Studi pembuatan aplikasi Psikolingua - Hasan Farisi; Anang Muftiadi; Iwan Sukoco (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The existence of a design thinking methodology that focuses on users/clients as objects of attention in product creation has an important role in the Sampul Kreatif company. Design thinking is applied as a method to solve user/client problems from the user's perspective (human centered), if it is associated with the service business run by Sampul Kreatif then this is an advantage. The purpose of this study is to describe the use of design thinking in software development service companies Sampul Kreatif when implementing it in making a software application called Psikolingua. Using literature studies to collect data and interviews with competent sources to validate research findings. The results obtained show that design thinking is an effective tool in creating a software application called Psikolingua that is needed by clients at the Sampul Kreatif company